2019
DOI: 10.1016/j.chom.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Utilization of Peptide Communication in Phages Infecting Soil and Pathogenic Bacteria

Abstract: Graphical Abstract Highlights d Arbitrium-like systems are common in phages infecting pathogens and soil bacteria d Peptide-based arbitrium communication regulates lysogeny in numerous phage types d Arbitrium systems are frequently encoded on mobile pathogenicity elements d A peptide-responsive non-coding RNA controls the regulator of the lysogenic state Authors Avigail Stokar-Avihail, Nitzan Tal, Zohar Erez, Anna Lopatina, Rotem Sorek Correspondence rotem.sorek@weizmann.ac.il In Brief Stokar-Avihail et al. di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
113
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 49 publications
2
113
2
Order By: Relevance
“…Hence, peptide communication is used to promote lysogeny when many infections have occurred. Similar arbitrium-like systems have now been found in a range of different phages [10]. Notably, these phages each use a slightly different signalling peptide, and do not seem to respond to the signals of other phages [9,10].The discovery of phage-encoded signalling peptides raises the question of how this viral communication system evolved.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Hence, peptide communication is used to promote lysogeny when many infections have occurred. Similar arbitrium-like systems have now been found in a range of different phages [10]. Notably, these phages each use a slightly different signalling peptide, and do not seem to respond to the signals of other phages [9,10].The discovery of phage-encoded signalling peptides raises the question of how this viral communication system evolved.…”
mentioning
confidence: 78%
“…Similar arbitrium-like systems have now been found in a range of different phages [10]. Notably, these phages each use a slightly different signalling peptide, and do not seem to respond to the signals of other phages [9,10].The discovery of phage-encoded signalling peptides raises the question of how this viral communication system evolved. While the arbitrium system has not yet been studied theoretically, previous work has considered the evolution of lysogeny and of other phage-phage interactions.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In B. thuringiensis the PlcR receptor is a transcription factor that becomes activated when bound to its cognate PapR peptide, leading to expression of virulence factors that facilitate infection of its insect larval host 27 . Such peptide-based communication was recently shown also to control the lysis-lysogeny decision of phages infecting many species of Bacillus 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Communication among phages through phage-encoded arbitrium peptides was first described by Erez et al 13 , and the following studies 14,[24][25][26] revealed the molecular basis for the production, detection, and consequences of the short signaling peptides on phages lysogeny-lysis decisions.…”
mentioning
confidence: 99%